Tooth Fairy - Gordon, Michael Lembeck; Twentieth Century Fox Film Corporation (United States Twentieth Century Fox Home Entertainment, 2010)
A minor league hockey player known for crushing dreams is magically sentenced to serve as a real tooth fairy, where he learns valuable lessons about hope, responsibility, and believing in dreams.
Originally released as a motion picture in 2010.
Rated PG.
Keywords: Fairies; Hockey players